Planning for offshore oil 2. - Memorial University of Newfoundland. Extension Service (MUN Extension Service, 1979)
Stanley Pickett explains the planning strategy and layout in Shetland as they prepared for the coming of the oil industry, and shows how this can be used in Newfoundland.